Preliminar performance of new oat and wheat genotypes in Central Depression of RS - Georg, Evandro S.; Carvalho, Fernando I. F. de; Barbosa, José F.; Franco, Francisco A.; Filho, Antonio W. P. Ferreira; Reis, Maurício S.; Viau, Luiz V. M. (Pesquisa Agropecuaria Brasileira, 2014)
More than two hundred oat and wheat advanced-lines selected in 1983 were grown in field experiments at Guaíba, RS, Brazil, in 1984. The objective was to quantify, grain yield, 100 grain weight, hectoliter weight, biological yield, heading time, and plant stature. The results were significant for all traits, indicating that selection was efficient in oats; on the other hand, only one wheat-line showed superiority to the best check-variety.
Keywords: genotype performance